Luciano Berioʼs “Folk Songs”: Reconstruction of the Idea in the Context of Creativity - Garmel, Oksana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. Luciano Berio’s vocal cycle «Folk Songs» for mezzo-soprano and seven instrumentalists (1964) was considered for the first time in Ukrainian musicology. The relevance of the research is determined by the imbalance between the high degree of performance demand of the work in the modern cultural space and the insignificant activity of its musicological study. The purpose of the study. The purpose of the article is to reconstruct the creative idea of the vocal cycle «Folk Songs» by Luciano Berio in the context of the composer’s searches, their mutual influences and interaction. Methods. The article uses historical, cultural and biographical methods (to study the stages of the formation of the idea of the work in the context of the composer’s creative biography), source studies (to find the sources of multinational folk songs that became the basis of the vocal cycle), methods of comparison and analogy (to propose a hypothesis about the origins of the creative idea of «Folk Songs») and the method of theoretical generalization. The results and conclusions. The biographical context and stages of creation of Luciano Berio’s «Folk Songs» are studied in detail, the sources of folk songs from five countries of the world (USA, France, Italy, Armenia, Azerbaijan) used by composer in the vocal cycle are determined. The main features of the formation of the unity of the cycle are considered: the general logic of the construction, the content of the texts, the composition of the instrumental ensemble, metro-rhythmic features. A hypothesis is proposed about the combined influence of the performing skills of Cathy Berberian and the linguistic and stylistic features of John Cage’s «Aria» (1958) on the formation of the idea of Luciano Berio’s «Folk Songs». The manifestation in the vocal cycle of Luciano Berio’s interest in the linguistic (phonological) aspect of creativity, which became active in his work from the 1950s, is emphasized. Based on the results of the research, it is proposed to perceive and realize «Folk Songs» as a link of two «lines» of Luciano Berio’s creative interests, manifested in his work — interest in multinational folklore and phonological features of different languages. Vocal cycles created in the 21st century based on the model of Luciano Berio’s «Folk Songs»: «Ayre» by Osvaldo Golijov, «Worksongs» by Samuel Blaser and «Chanzuns Popularas Romanchas» by Oscar Strasnoy were identified. These works indicate possible prospects for the continuation of the research topic.